2019
DOI: 10.1016/j.ijpara.2019.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of cryptosporidiosis due to Cryptosporidium parvum subtype IIdA19G1 in neonatal calves on a dairy farm in China

Abstract: a b s t r a c tNeonatal diarrhea is one of the most important syndromes in dairy cattle. Among enteropathogens, Cryptosporidium spp. are primary causes of diarrhea, but outbreaks due to cryptosporidiosis are rarely reported in cattle. From January to April in 2016, severe diarrhea was observed in over 400 neonatal dairy calves on a large dairy farm in Jiangsu Province of East China. Approximately 360 calves died due to watery diarrhea despite antibiotic therapy. In this study, 18 fecal specimens were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 33 publications
2
60
0
Order By: Relevance
“…Our ndings indicate that C. parvum was clearly predominant in every season, whereas C. bovis and C. ryanae were found only occasionally. This is similar to two studies of cryptosporidiosis outbreaks in Ningxia and Jiangsu, in which the occurrence of C. parvum was signi cantly higher than that of C. bovis or C. ryanae [10,11]. Subtyping C. parvum revealed two zoonotic subtypes, IIdA14G1 and IIdA15G1.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Our ndings indicate that C. parvum was clearly predominant in every season, whereas C. bovis and C. ryanae were found only occasionally. This is similar to two studies of cryptosporidiosis outbreaks in Ningxia and Jiangsu, in which the occurrence of C. parvum was signi cantly higher than that of C. bovis or C. ryanae [10,11]. Subtyping C. parvum revealed two zoonotic subtypes, IIdA14G1 and IIdA15G1.…”
Section: Discussionsupporting
confidence: 88%
“…In general, Cryptosporidium was signi cantly associated with calves younger than 2 weeks with diarrhea [29]. A previous study of a diarrhea outbreak among neonatal dairy calves in Jiangsu suggested that the prevalence of Cryptosporidium was signi cantly higher during the outbreak (80.3%) than after the outbreak (22.7%), and that the prevalence of Cryptosporidium in dairy calves less than 3 weeks old was much higher than in any other age group [11]. In a similar cryptosporidiosis outbreak in Ningxia, the highest prevalence of Cryptosporidium (83.3%, 40/48) was seen in 2-3-week-old calves with severe diarrhea [10].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Gansu Provinces [9,11,12,[17][18][19]23]. Subtype IIdA19G1 was mostly found in Jiangsu, Henan, Shanghai, Xinjiang, Guangdong, Hebei, Tianjin, Beijing, and Heilongjiang Provinces [10,14,15,[21][22][23]25]. Subtype IIdA20G1 was found in Heilongjiang Province [11].…”
Section: Discussionmentioning
confidence: 99%